High prevalence of Panton-Valentine Leucocidin (PVL) toxin carrying MRSA and multidrug resistant gram negative bacteria in late onset neonatal sepsis indicate nosocomial spread in a Pakistani tertiary care hospital. Issue 2 (February 2023) - Zahoor, Zainab; Mumtaz, Amna; Farooqi, Zia-ur-Rehman; Rehman, Noor; Batool, Nighat; Noreen, Zobia; Sattar, Sadia; Bostan, Nazish; Javed, Sundus
Abstract: Background: Neonatal sepsis has high incidence with significant mortality and morbidity rates in Pakistan. We investigated common etiological patterns of neonatal sepsis at a tertiary care setup. Methods: 90 pus and blood, gram negative and gram positive bacterial isolates were analyzed for virulence and antibiotic resistance gene profiling using PCR and disc diffusion methods. Results: Staphylococcus aureus showed strong association with neonatal sepsis (43 %) followed by Citrobacter freundii (21 %), Pseudomonas aeruginosa (13 %), Escherichia coli (15 %) and Salmonella enterica (8 %). Molecular typing of E. coli isolates depicted high prevalence of the virulent F and B2 phylogroups, with 4 hypervirulent phylogroup G isolates. 76.9 % S. aureus isolates showed presence of Luk-PV, encoding for Panton-valentine leucocidin (PVL) toxin with majority also carrying MecA gene and classified as methicillin resistant S. aureus (MRSA) . ecpA, papC, fimH and traT virulence genes were detected in E. coli and Salmonella isolates. 47 % Citrobacter freundii isolates carried the shiga like toxin SltII B . Antimicrobial resistance profiling depicted common resistance to cephalosporins, beta lactams and fluoroquinolones. Conclusion: Presence of PVL carrying MRSA and multidrug resistant gram negative bacteria, all isolated from late onset sepsis neonates indicate a predominant nosocomial transmission pattern which may complicate management of the disease in NICU setups